Biomedical Dermatology - An, Sungkwan; Dong, Yinmao
Biomedical Dermatology brings together basic, pre-clinical and clinical research on the biology of the skin and biomedical aspects of dermatology and cosmetology. The journal is the official journal of the Korea Institute of Dermatological Sciences (KIDS), which specializes in all areas of dermatology and cosmetic biology and biotechnology research. The journal aims to be a high quality international forum for innovative and exciting advances in dermatology and cosmetology. Topics of interest include, but are not limited to:Ÿ Cellular and molecular biology of skin Prevention, diagnosis and management of disorders of the skin, hair and nails Effects of cosmetic compounds on skin biology Chinese medicine and its application for cosmetology and dermatology Skin immunology and physiology Alternatives to animal experiments and tissue engineering Regenerative medicine and stem cell research related to skin.